2004
DOI: 10.1590/s1516-14392004000100007
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime modelling for MCrAlY coatings in industrial gas turbine blades

Abstract: A novel theoretical and experimental approach for lifetime modelling of MCrAlY coatings for stationary gas turbines has been undertaken using the Inverse Problem Solution (IPS) technique. With this technique feasible experimental data acquired after a defined experimental time t e are used as input values for the model parameters estimation. In the first stage of the approach a model, based on the oxidation and diffusion processes (Fick's first and second law) was assumed, which considers the Al concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Toscano et al (Ref 28) have reported the coexistence of the c phase with the r-(Co,Cr) phase in samples of a similar CoNiCrAlY coating that had been annealed at 800°C for 300 h. However, since the Co-to-Cr ratio in the Cr-rich phase was very low, it was assumed that it was a-Cr rather than r-(Co,Cr) which would have had a higher Co-to-Cr ratio. Toscano et al carried out their annealing process on an attached coating, so that interdiffusion between substrate and coating may have changed the coating composition ( Ref 25,29,30). Also their annealing process was carried out in air which will cause some oxidation of the coating and hence loss of elements, such as Al, Cr, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Toscano et al (Ref 28) have reported the coexistence of the c phase with the r-(Co,Cr) phase in samples of a similar CoNiCrAlY coating that had been annealed at 800°C for 300 h. However, since the Co-to-Cr ratio in the Cr-rich phase was very low, it was assumed that it was a-Cr rather than r-(Co,Cr) which would have had a higher Co-to-Cr ratio. Toscano et al carried out their annealing process on an attached coating, so that interdiffusion between substrate and coating may have changed the coating composition ( Ref 25,29,30). Also their annealing process was carried out in air which will cause some oxidation of the coating and hence loss of elements, such as Al, Cr, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the goal was to use the results of experimental studies in an attempt to estimate the model parameters allowing to ascertain the lifetime of the coating through the inverse problem solution (IPS) approach. The IPS was successfully employed in the past to estimate the lifetime of MCrAlY coatings all by considering the phase transformations occurring in the coating and its oxidation . Usually the diffusion coefficients in metals are not accurately known for particular conditions (alloy composition and temperature), which obstruct the modeling and the estimation of lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Only the concentration of the main species is calculated. Oxidation in this work is not considered but it can be taken into account as outgoing flux calculated assuming, for instance, parabolic growth law .…”
Section: Introductionmentioning
confidence: 99%
“…During high temperature exposure, a thin layer of protective α-Al2O3 formed on the coating surface, which serves as a diffusion barrier between the environment and underlying alloy [6]. The depletion rate of β phase in MCrAlY has been used as a criterion by many investigators [7][8][9][10][11] to evaluate the end of coating lifetime. However, the complete depletion of β phase doesn't necessarily mean the end of coating life.…”
Section: Introductionmentioning
confidence: 99%